PENGELOLAAN ELECTRONIC GOVERNMENT MELALUI E-PPID DALAM MENDUKUNG TATA KELOLA INFORMASI PUBLIK DI BAWASLU DAERAH ISTIMEWA YOGYAKARTA - Syariza; Hanantyo Sri Nugroho (Journal Publicuho, 2025)
The purpose of this research is to describe and analyze how the management of electronic government in supporting public information governance by the General Election Supervisory Agency of the Special Region of Yogyakarta, as well as analyzing the factors that become challenges and obstacles in realizing public information transparency through E-PPID management. This research uses a qualitative method with a descriptive approach. To answer these problems and research objectives, researchers used the theory of successful elements of e-government development in the Harvard JFK School of Government, namely: support, capacity, and value. The results showed that the management of electronic government in supporting public information governance in the General Election Supervisory Agency of the Special Region of Yogyakarta has been running well. However, in the development of e-government, there are still several obstacles, namely the availability of limited financial resources so that socialization is not optimal and system maintenance is not optimal. The efforts needed are to socialize E-PPID to the wider community both directly and online and to carry out regular system maintenance to avoid things that can harm the institution.